Effects of microRNA-320 on learning and memory in mice with vascular cognitive impairment caused via cerebral ischemia: MiR-320 and vascular cognitive impairment induced via cerebral ischemia - Yu, Kunqiang; Xu, Ri; Wu, Lixu; Li, Weiwei; Lin, Ruhui; Dai, Mengyuan; Ma, Xu (Cellular and Molecular Biology, 2023)
We aimed to explore microRNA (miR)-320's impacts on learning and memory in mice with vascular cognitive impairment induced via cerebral ischemia. After establishment of a cerebral small vessel disease (CSVD) cognitive impairment model, application of corresponding treatment methods was in the model mice to inject miR-320 antagomir/agomir and their negative controls to the lateral ventricles: Test of the learning and memory abilities of mice was conducted; Detection of oxidative stress, inflammation, miR-320, Vascular endothelial growth factor (VEGF) and endostatin (ES) was implemented; Taking mouse hippocampal neuron cells was to detect the cell advancement. MiR-320 was elevated in the CSVD model; MiR-320 was negatively linked with the learning and memory abilities of mice; Repressing miR-320 was available to memorably elevate the learning and memory abilities of CSVD mice; Depressing miR-320 clearly drove CSVD mouse neovascular protein VEGF, but reduced inflammation, oxidative stress response and ES; Restraining miR-320 was available to contribute to mouse neuronal cell advancement. MiR-320 mitigates the learning and memory abilities of cerebral ischemia-induced vascular cognitive dysfunction mice to a certain extent.